The Archaeometallurgical Evaluation of Three Bronze Socketed Axes, Discovered in Eastern Romania - Viorica Vasilache; Vasile Diaconu; Otilia Mircea; Ana Drob; Ion Sandu (Applied Sciences, 2021)
This paper presents the study of three bronze socketed axes discovered in Neamţ County, Romania. The surface structures and those from the interface of the corrosion layer with the metal core of the basic alloy were analyzed, in order to elucidate the nature of the materials used and the manufacturing processes. The analyzes by optical microscopy (OM) and electron microscopy (SEM), coupled with X-ray spectrometry (EDX), revealed the type of their degradation during the depositional period, as a result of the processes of chemical alteration and physical damage. A series of metallurgical techniques used were also established, as well as the identification of some finishing and decoration processes that led to the establishment of the objects’ functionality.